Pengelolaan Keuangan Keluarga Secara Profesional Dalam Mewujudkan Keluarga Sakinah - Syaparuddin, Dr. (Pasca Sarjana STAIN Watampone, 2014)
This study aims to discuss about financial management for family profesionally which is based on the prinsiples of Islam. The financial management for family is very urgent to discuss deeply because it became one of very important instruments to realize a happy family according to Islam. If this could be appllied well, broken home in a family which will bring divorce could be avoided as minimal as possible. In Islam, managing money should be directed to realize virtue as much as possible. Based on this, we have to spend our money to realize virture. This attitude will give us a framework that according to Islam making financial planning for family profesionally has to reach a very nice top goal called FALAH (living prosperously in the world and in the hereafter), avoiding gambling, avoiding monkey business, avoiding usuary, avoding exploitation for someone else, prefering alms giving, and avoiding wasful nature.